A statistical technique for determination of withdrawal of northeast monsoon over coastal Tamilnadu - RAJ, Y. E. A. (MAUSAM, 1998)
The withdrawal dates of northeast monsoon over coastal Tamil Nadu for the 90-year period (1901-90) have been objectively derived. The methodology of determination was generally based on an index based on the spatial distribution of daily rainfall over stations of coastal Tamil Nadu, over a 5-day pentad for the six month period, September- February. The normal withdrawal date thus obtained was 27 December with a standard deviation of 13.6 days and range 23 November-28 January. The duration of northeast monsoon was distributed with mean 67.5 days, standard deviation 14.9 days and range 26-102 days. During 36.7 % of years the withdrawal spilled over to January of next year. The daily normal rainfall and its difference filter have been discussed with reference to the normal date of withdrawal. The average decrease of rainfall at the time of withdrawal has been derived by application of superposed epoch analysis. It has further been shown that during years when the withdrawal took place in January the intensity of northeast monsoon prior to withdrawal was as intense as in years when withdrawal occurred in December. A few cases of northeast monsoon withdrawal have been illustrated with diagrams. As no definite dynamic or thermodynamic features could be uniquely identified which are associated with the withdrawal, this technique is basically statistical, considering the behaviour of the daily normal rainfall as the sole criterion. Unique thermodynamic and dynamic features are not identifiable which are associated with the withdrawal of northeast monsoon over coastal Tamilnadu.